An analysis of education principle implementation in an online counseling approach: a preliminary study based on analysis using the Rasch model - Ardi, Zadrian (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2019)
Education is an important human activity, and a fundamental right of every human. There has been a continuous transformation of educational counseling methods and processes to improve them. However, research about the application of educational principles to long-distance counseling has not been available until now. This research aims to study the implementation of educational principles in the online counseling process with the Rasch model. The sample size of this study is 174 people, spread across Indonesia with varying demographics. The results of the study show that the application of educational principles in online counseling services significantly suppresses the problematic conditions of respondents. The study also examines how online counseling services serves as a quick help or first aid to problematic conditions experienced by clients. The implementation of the educational principles discussed in this study relates to the development of self-potential, self-control, personality development, independence development and development of self-intelligence and other skills.